Delving into the digital divide. - Venkat, K. (IEEE spectrum)
The author examines the question of whether the digital divide due to poverty or an effect of underlying social and economic conditions. The digital divide is a major concern to technology companies, because it bars billions of people from buying their products. But it is difficult for industry to tap this market potential without addressing poverty as an issue. Microsoft chairman Bill Gates has publicly stated that he does not see the rural poor in developing countries as a significant business opportunity